UJI KONSENTRASI PENGHAMBATANDAN PENGGUNAAN ANTIBIOTIK UNTUK MENANGGULANGI PENYAKIT MOTIL AEROMONAS SEPFISEMIA (MAS) PADA LELE DUMBO (Claria gariepinus) MINIMAL INHIBITORY CONCEIENTRATION (MIC) AND - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1996)
ABSTRACT: Five isolates of A. hydrophila were used for MIC, and resistency tests to rifampicin, kanamycin, chloramphenicol, erythromycin and oxytetracyclin by dilution method with TSB medium. The results indicated that the bacteria had various degref of sensitivity to these antibiotics. Resistency of bacteria isolates increased 1.3 to 62 times after they were passaged three times to MIC of the drugs or antibiotics by dilution method. Other test was kanamycin medication conducted by i.p. injection, immersion and oral methods. The results showed that all kanamycin medication methods were effective to decrease mortality rates caused by A. hydrophila infection. Oral medicaton method was the most effective compared to other methods because this method could minimize stress during handling. However, oral medication took much longer time (15 days) than immersion and injection methods (few minutes).